STUDY OF EFFECTIVNESS OF SEDIMENT CONTROL OF THE PABELAN RIVER POST OF 2010 MERAPI MOUNTAIN ERUPTION IN MAGELANG DISTRICT - Aprilian, Zeolita
Mount Merapi is one of the most active volcanoes in Indonesia, with an eruption period of 4 (four) years, and the eruption in 2010 was a major eruption that occurs once every 100 years. The eruption in 2010 released sediment in the form of sand and rocks, totaling approximately 140 million m3. The material, together with rainfall, was distributed to 15 (fifteen) rivers originating from Mount Merapi, one of which is the Pabelan River. According to the 2010 BNPB lahar potential map, the Pabelan River has the potential to receive 24 million m3 of lahar resulting from the eruption of Mount Merapi. To minimize losses and as an effort to mitigate the disaster caused by debris floods, BBWS Serayu Opak built the Menayu PA-C Sabo Dam on the Pabelan River in 2022. This study was conducted to assess the effectiveness of sediment control in the Pabelan River before and after the construction of the new Sabo Dam. Hydrological calculations were performed using HEC-HMS with topographic analysis using ArcGIS 10.6.1, 2D hydraulic analysis using HEC-RAS 6.3.1 with Non-Newtonian and Kanako 1.44 features to perform erosion and sedimentation analyses. Debris floods were generated from daily rainfall data, and the debris flood event on February 3, 2011, was used to determine the calibration parameters for erosion and sedimentation analysis using 2020 river geometry data. The research results indicate that the debris flow on February 3, 2011, was caused by a rainfall of 96 mm, which was below the 2-year recurrence interval of 117.814 mm. The analysis of erosion and sedimentation shows that there has been a significant change in the channel bed of the Pabelan River from upstream to downstream due to massive sedimentation after the eruption of Mount Merapi, ranging from 1-17 meters. Based on the 1D sedimentation and erosion analysis, the construction of 24 effective Sabo dams can hold sediment in the Pabelan River and reduce the amount of sediment that passes downstream by 0.7%. However, this reduction in sedimentation is not significant due to the upstream Sabo dams already being filled, hence regular maintenance is needed to maximize the function of the Sabo dams. The addition of two Sabo dams from 22 to 24 is effective in reducing the potential for debris flow as a mitigation measure against disasters caused by the eruption of Mount Merapi. This is seen from the results of the 2D modeling scenarios 1 and 2 at observation points 1 and 2 (residential areas), where the channel is still capable of holding debris flow and there is no overflow.